MATEC Web of Conferences - Dubkova, Ya (EDP Sciences, 2018)
The ballistic characteristics of the mixture compositions containing aluminum powder ASD-6M have been studied. It is shown that the activation of aluminum powder by microwave radiation leads to an increase in the combustion heat of the mixture composition by 11%.